Palladium‐Catalyzed Electrophilic Functionalization of Pyridine Derivatives through Phosphonium Salts. (15th July 2020) - Che, Yuan‐Yuan; Yue, Yanni; Lin, Ling‐Zhi; Pei, Bingbing; Deng, Xuezu; Feng, Chao
Abstract: Herein, we report a highly efficient and practical method for pyridine‐derived heterobiaryl synthesis through palladium‐catalyzed electrophilic functionalization of easily available pyridine‐derived quaternary phosphonium salts. The nice generality of this reaction was goes beyond arylation, enabling facile incorporation of diverse carbon‐based fragments, including alkenyl, alkynyl, and also allyl fragments, onto the pyridine core. Notably, the silver salt additive is revealed to be of vital importance for the success of this transformation and its pivotal role as transmetallation mediator, which guarantees a smooth transfer of pyridyl group to palladium intermediate, is also described. Abstract : It takes two : By taking advantage of the synergistic interaction of a palladium catalyst and silver additive, a strategically novel synthetic method that enables the expedient site‐selective elaboration of pyridine derivatives was developed. The successful use of pyridylphosphonium salts as donors of a pyridyl anion equivalent greatly expands the range of competent nucleophilic coupling partners for palladium‐catalyzed cross‐coupling.